2014
DOI: 10.1371/journal.pone.0092535
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for Seed Vigor-Related Traits Identified in Maize Seeds Germinated under Artificial Aging Conditions

Abstract: High seed vigor is important for agricultural production due to the associated potential for increased growth and productivity. However, a better understanding of the underlying molecular mechanisms is required because the genetic basis for seed vigor remains unknown. We used single-nucleotide polymorphism (SNP) markers to map quantitative trait loci (QTLs) for four seed vigor traits in two connected recombinant inbred line (RIL) maize populations under four treatment conditions during seed germination. Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 57 publications
8
62
0
2
Order By: Relevance
“…Specific bands produced by SSR markers Satt371, Satt453 and Satt618 make them candidate markers for linkage with seed storability and testa colour (Hosamani et al 2013). The last decade has also seen research directed towards the inference of the genetic basis of seed deterioration through investigation of quantitative trait loci associated with seed longevity (Han et al 2014). Seed ageing is a complex biological trait and difficult to monitor.…”
Section: Seed Quality Parametersmentioning
confidence: 99%
“…Specific bands produced by SSR markers Satt371, Satt453 and Satt618 make them candidate markers for linkage with seed storability and testa colour (Hosamani et al 2013). The last decade has also seen research directed towards the inference of the genetic basis of seed deterioration through investigation of quantitative trait loci associated with seed longevity (Han et al 2014). Seed ageing is a complex biological trait and difficult to monitor.…”
Section: Seed Quality Parametersmentioning
confidence: 99%
“…This trait is controlled by many QTLs that are located on different chromosomes, as found in the model plant Arabidopsis (Clerkx et al, 2004) and in crop plants such as rice (Cui et al, 2002; Miura et al, 2002), Medicago truncatula (Vandecasteele et al, 2011), and maize (Han et al, 2014) and is also affected by environmental factors during seed development, harvest, and storage.…”
Section: Introductionmentioning
confidence: 99%
“…From many seed deterioration experiments, QTLs of seed longevity traits like LD 50 in Arabidopsis seeds [21], germination of aged wheat seeds [48,49] and half-life (P 50 ) of aging barley seeds [50] have been mapped and linked to various genes. For the germination vigor of seeds, several seed priming experiments have found QTLs for germination of maize seeds [51] and QTLs for 30 vigor traits of rice seeds [52] to mention a few. These studies also provided useful information on chromosome regions and putative genes controlling various seed vigor traits in different crops.…”
Section: Mapping the Genes Controlling Seed Aging/vigormentioning
confidence: 99%
“…Nagel et al [50] also reported large QTL effects associated with seed half-life (P 50 ) on chromosomes 5 and 7 in a doubled haploid mapping population of barley. Han et al [51] found 65 QTLs in two maize populations mapped using single-nucleotide polymorphism (SNP) markers to four seed vigor traits under four germination treatment conditions. Integrating the QTLs into 18 meta-QTLs (mQTLs), 23 candidate genes associating with seed vigor phenotype coincides with 13 mQTLs controlling protein metabolism and the glycolytic pathway.…”
Section: Mapping the Genes Controlling Seed Aging/vigormentioning
confidence: 99%